2018
DOI: 10.1016/j.bjm.2017.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Bioflocculant production from Streptomyces platensis and its potential for river and waste water treatment

Abstract: A bacterium isolated from Sterkfontein dam was confirmed to produce bioflocculant with excellent flocculation activity. The 16S rDNA nucleotide sequence analyses revealed the bacteria to have 99% similarity to Streptomyces platensis strain HBUM174787 and the sequence was deposited in the Genbank as Streptomyces platensis with accession number FJ 486385.1. Culture conditions for optimal production of the bioflocculant included glucose as a sole carbon source, resulting in flocculating activity of 90%. Other opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 40 publications
2
18
0
Order By: Relevance
“…All three lentil extracts were highly carbonaceous materials which mainly made up of carbon and oxygen. The elemental composition results were found to be in close agreement with the natural coagulant reported by R. Ahmad and Haseeb [14] and Agunbiade et al [15] where carbon and oxygen were the major components for natural coagulant. Some inorganic elements, i.e., calcium (Ca) was detected in trace amount for red lentil extract and potassium (K) for red and brown lentil extracts.…”
Section: Elemental Compositions Of the Lentilssupporting
confidence: 88%
“…All three lentil extracts were highly carbonaceous materials which mainly made up of carbon and oxygen. The elemental composition results were found to be in close agreement with the natural coagulant reported by R. Ahmad and Haseeb [14] and Agunbiade et al [15] where carbon and oxygen were the major components for natural coagulant. Some inorganic elements, i.e., calcium (Ca) was detected in trace amount for red lentil extract and potassium (K) for red and brown lentil extracts.…”
Section: Elemental Compositions Of the Lentilssupporting
confidence: 88%
“…Similarly, higher removal percentages of nitrate, phosphates, and COD were reported to associate with bioflocculation process of microalgae [13,18,19,38]. In general, algal cell density in flocculation forms is always higher than free forms [20,21]. e high removal efficiency in wastewater treatment with AFL could be attributed to the availability of sufficient oxygen for further mineralization of organic carbon and nutrients because of the high concentration of microalga cells in flocculation formation.…”
Section: Removal Of Bod 5 and Codmentioning
confidence: 94%
“…erefore, MBF and FAMP have been used to improve nutrient removal and effluent recovery in aerobic-activated sludge technologies [13,15,17]. e bioflocculation of microalgae and bacteria have been intensively studied and reviewed for recent advances and perspectives [18][19][20]. Besides, MBF can be used as a promising low-cost method for harvesting microalga biomass [14,21].…”
Section: Introductionmentioning
confidence: 99%
“…This explains the presence of carbon and oxygen structures, as per the FTIR results. Often, carbon and oxygen are the major compositions in bioflocculants such as guar gum [32] and Streptomyces platensis [33]. Bello, et al [34] and Xiong, et al [35] reported that polymers with a high composition of carbon generally exhibit good adsorption ability.…”
Section: Elemental Compositionmentioning
confidence: 99%